Challenges in conducting online classes during the Covid-19 pandemic: Perspectives from six European countries - Dadić Fruk, Lorena (Oeconomica Jadertina, 2023)
Online teaching can provide teachers and students numerous benefits if they are familiar with the tools, techniques and methods for its implementation. Due to the situation caused by the Covid-19 virus pandemic, teachers had to move all activities to an online environment in a very short time, regardless of their familiarity and experience with distance teaching. As a result, teachers found themselves in an unfavourable situation and faced a number of challenges they had to overcome in a short period of time and in a way that did not jeopardize the quality of online teaching. The aim of this paper is to investigate the key challenges in online teaching during the pandemic from the perspective of university teachers in six European countries. For this purpose, an online survey was conducted using a structured questionnaire on a sample of 525 teachers from higher education institutions in six European countries. The research was conducted from May to October 2021. The results showed that the main challenges faced by teachers in the online environment were mainly in conducting tests and using certain software and applications. During online teaching, the biggest challenge for teachers was the transfer of knowledge to students related not only to general skills, such as the ability to work independently, problem-solving skills, data collection and data processing, but also skills related to learning, such as how to prepare for a lecture and how to write and read academic papers. Despite a wide range of challenges that teachers faced in this new environment, they were still able to solve most of the challenges, mainly by independently searching for information on the Internet and consulting colleagues, but also using assistance provided by universities, faculties and technical services that also played an important role in problem solving.
Keywords: online teaching; COVID-19; distance learning; information and communication technologies